Sheikh Shabbir Ahmad Al-Uthmani’s Contributions in Explaining the Oneness of God’s Essence and Worship - Syed Shahrukh Kamal; Dr. Abdul Wahab Jan al-Azhari (Journal of Religion and Society, 2025)
This article explores the theological contributions of ʿAllāma Shabbīr Aḥmad al-ʿUsmānī, one of the leading scholars of the Indian subcontinent, focusing specifically on his efforts in affirming the oneness of God (Tawḥīd) and refuting polytheism (Shirk). Drawing upon his key works including Fatḥ al-Mulhim, his tafsīr of the Qurʾān, and his treatise al-Islām the article highlights his rational and textual methodology in establishing Tawḥīd al-Dhāt (Oneness of God’s Essence) and its practical extension, Tawḥīd al-ʿIbādah (Oneness in Worship). The study further presents his critique of historical and contemporary forms of polytheism, offering a robust intellectual framework rooted in the teachings of the Salaf and aligning with the creed of Ahl al-Sunnah wa-l-Jamāʿah. The article also reflects on the relevance of al-ʿUthmānī’s emphasis on Tawḥīd in contemporary contexts, where theological confusion and popular forms of shirk persist. His methodological clarity serves as a model for reestablishing pure Islamic monotheism in both educational discourse and daʿwah efforts. Keywords: Tawḥīd, Shabbīr Aḥmad al-ʿUsmānī, Tawḥīd al-Dhāt, Tawḥīd al-ʿIbādah, Shirk, Ilāhiyyāt, Ahl al-Sunnah wa-l-Jamāʿah